Peningkatan Produktivitas Kelompok Nelayan Semoga Jaya Dengan Memanfaatkan Alat Pengering Ikan Tenaga Surya Kontrol Temperatur Otomatis - Oknovia Susanti; Arib M. Jahfal; M. Rifqi Anugrah; Arni Amir; Endri Yani (Jurnal Hilirisasi IPTEKS, 2025)
The fishermen face various obstacles in the fish drying process, as they still rely on traditional methods that are highly influenced by the weather, take a long time, and are prone to contamination from dust and insects. To overcome these problems, the community service team developed a solar-powered fish dryer equipped with a solar collector. This device is designed to improve the efficiency, quality, and hygiene of the fish drying process. The stages of the activity included field surveys, device design, device manufacturing, training in use, and device performance evaluation. The solar-powered fish drying device is able to overcome the limitations of traditional methods and produce faster and more hygienic drying results. The results of the activity show that the average wet fish catch of fishermen reaches 30 kg, which after drying produces about 8 kg of dried fish. The drying process using solar-powered equipment can produce dried fish within 24 hours, which is much faster than the traditional sun-drying method that takes 48 hours or 2-3 days depending on weather conditions. Time efficiency is increased by up to 50%, while the quality of the fish is better preserved because it is protected from environmental contamination. In addition, this device ensures a consistent level of shrinkage in dried fish, which is around 26-27% of the initial weight, thus providing more stable results for fishermen. Overall, this activity has succeeded in increasing the effectiveness of dried fish processing, improving product quality, and enhancing the competitiveness of coastal fishermen.